2019
DOI: 10.1111/jop.12956
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for classification of oropharyngeal squamous cell carcinoma: Morphology and status of HPV by immunohistochemistry and molecular biology

Abstract: The current three‐tier grading system (well, moderate and poorly differentiated) used to morphologically classify head and neck squamous cell carcinoma (HNSCC) is inadequate for categorisation of oropharyngeal squamous cell carcinoma (OPSCC) owing to the lack of prognostic value. The aim of this study was to assess the validity of a classification system for OPSCC based on morphology and human papilloma virus (HPV) infection status. Haematoxylin and eosin slides of 121 patients (100 M, 21 F, age range 40‐89 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Reference to negative controls is necessary to distinguish low HPV transcript signals from non-specific punctate staining. [26][27][28] We show that such control tissue must be stained on the same slide as the test tissue, since in this study we observed heterogeneity in…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Reference to negative controls is necessary to distinguish low HPV transcript signals from non-specific punctate staining. [26][27][28] We show that such control tissue must be stained on the same slide as the test tissue, since in this study we observed heterogeneity in…”
Section: Discussionmentioning
confidence: 70%
“…In keeping with the observation by Rooper et al, 19 all discordant cases in our study were restricted to cases with low signal intensity and/or transcript number indicating the necessity for observer training and calibration in RNA ISH interpretation. Reference to negative controls is necessary to distinguish low HPV transcript signals from non‐specific punctate staining 26‐28 . We show that such control tissue must be stained on the same slide as the test tissue, since in this study we observed heterogeneity in staining patterns of serial sections placed on different slides during the same test run.…”
Section: Discussionmentioning
confidence: 71%
“…All cases show non-keratinized (“basaloid”) and mixed-type (“keratinized” and “basaloid”) SCC morphology [ 32 ] and positive p16 immunohistochemical staining according to the Lewis et al, criteria ( Figure 1 b) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies about RNA ISH have been rising in the last 10 years and showing excellent diagnostic performances. Sensitivities vary from 87 to 100%, and specificities vary from 88 to 100%, being more frequently around 95% ( 62 65 , 69 72 ). Importantly, studies using RT-PCR as the reference test found the best diagnostic performances, making RNA ISH the method of choice for detecting high-risk HPV infections ( 62 , 65 , 71 ).…”
Section: Main Techniques Used To Detect Hpv In Opsccmentioning
confidence: 99%